2015
DOI: 10.1111/febs.13201
|View full text |Cite
|
Sign up to set email alerts
|

Pliable natural biocide: Jaburetox is an intrinsically disordered insecticidal and fungicidal polypeptide derived from jack bean urease

Abstract: Jaburetox is a polypeptide derived from jack bean (Canavalia ensiformis) urease and toxic to a broad spectrum of insects, phytopathogenic filamentous fungi and yeasts of medical importance. The elucidation of the structural basis for the mode of action of Jaburetox is the focus of this multifaceted study. Jaburetox in solution is a monomer of 11.0 kDa featuring a large hydrodynamic radius, suggestive of a disordered polypeptide. The intrinsically disordered nature of Jaburetox was theoretically predicted by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 110 publications
0
38
0
Order By: Relevance
“…The recombinant peptide Jbtx was expressed and purified as described by Lopes et al (2015) with minor modification. After the purification, Jbtx was extensively dialyzed against Tris buffer (500 mM Tris‐HCl, 100 mM MgCl 2 , 0.02% sodium azide), pH 7.5.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant peptide Jbtx was expressed and purified as described by Lopes et al (2015) with minor modification. After the purification, Jbtx was extensively dialyzed against Tris buffer (500 mM Tris‐HCl, 100 mM MgCl 2 , 0.02% sodium azide), pH 7.5.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant peptide Jaburetox (without a fused V5-antigen) was expressed and purified as described by Lopes et al [ 26 ] with modifications. Escherichia coli BL21 (DE3) RIL harboring the plasmid pET23a-Jaburetox was cultured in 20 ml LB (Luria Bertani) Broth, with 100 μg/ml ampicillin and 40 μg/ml chloramphenicol.…”
Section: Methodsmentioning
confidence: 99%
“…A large hydrodynamic radius, together with light scattering, CD and NMR spectroscopic data, shows that Jaburetox is a monomeric disordered peptide with an -helix motif by its N-terminus and two turn-like structures in the central region and by the C-terminus of the peptide. It is suggested that the Jaburetox IDP might act as a membrane protein and/or as a scaffold protein, but evidence for this is still lacking, therefore a comprehensive view of its insecticidal activity remains elusive [136].…”
Section: Jaburetox An Intrinsically Disordered Insecticidal Polypeptidementioning
confidence: 99%